The Global Economic Ethic Manifesto: Implementing a Moral Values Foundation in the Multinational Enterprise - Hemphill, Thomas A.; Lillevik, Waheeda (2011)
The Global Economic Ethic Manifesto (“Manifesto”) is a moral framework/code of conduct which is both interactive and interdependent with the economic function of the main institutions of the economic system: markets, governments, civil society, and supranational organizations, which lays out a common fundamental vision of what is legitimate, just, and fair in economic activities. The Manifesto includes five universally accepted principles and values: the principle of humanity; the basic values of non-violence and respect for life; the basic values of justice and humanity; the basic values of honesty and tolerance; and the basic values of mutual esteem and partnership. We posit that the Manifesto provides an ethical foundation for explicitly assisting multinational enterprise's (“MNE”) executive management and boards of directors to meet the moral failures criticisms associated with the expansion of global capitalism, and similarly how the U.N. Global Compact (“Compact”) is focused on addressing complimentary market and institutional failures. In this article, we argue how the Compact and the Manifesto complement each other, explaining how the policies and guidelines of the Compact can now be implemented at the organizational/individual level through a comprehensive human resource management (HRM) plan supporting the ethical framework of the Manifesto. Finally, we have described how the Manifesto completes a comprehensive managerial framework (consisting of both the Compact and the Manifesto) for what we term an “MNE Moral Values-Based Corporate Governance Model.” Ultimately, further research is needed in understanding how much impact external and internal influences make on creating a sustainable ethical culture in MNEs.
Keywords: United Nations Global Compact; Multinational Enterprise; moral values; Human Resource Management; Global Economic Ethic Manifesto; Corporate Governance